2020
DOI: 10.1371/journal.pone.0240243
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative anemia is a risk factor for acute kidney injury after open aorta and vena cava surgeries

Abstract: Open aorta and vena cava surgeries are usually associated with substantial blood loss which may result in postoperative acute kidney injury (AKI). The present study is designed to investigate the prevalence, outcome and risk factors of postoperative AKI associated with open aorta and vena cava surgeries, with a focus on the role of anemia in these conditions. A retrospective review of medical records of Peking Union Medical College Hospital was conducted. Patients who underwent open aorta and vena cava surgeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The ICU is a place to rescue severely ill patients, and most patients suffer from multiple organ failure. It has been reported that the mortality rate of patients with more than 2 failed organs is more than 50%, and that of patients with more than 4 failed organs is 100%, which seriously affects the quality of life and safety of patients[ 3 , 4 ]. Studies have shown that the release of proinflammatory mediators is increased in severely ill patients, and then tissue replacement downregulates the release of proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…The ICU is a place to rescue severely ill patients, and most patients suffer from multiple organ failure. It has been reported that the mortality rate of patients with more than 2 failed organs is more than 50%, and that of patients with more than 4 failed organs is 100%, which seriously affects the quality of life and safety of patients[ 3 , 4 ]. Studies have shown that the release of proinflammatory mediators is increased in severely ill patients, and then tissue replacement downregulates the release of proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Significant blood loss from trauma itself can lead to overall decreased kidney perfusion, which also subsequently will lead to kidney ischemia and AKI, and this significant blood loss can be reflected as a low hemoglobin level as well. Since the 1950s and more recent observational studies have also found that anemia is an acute predictor of AKI [23][24][25][26].…”
Section: Table 2 Socioeconomic Status Variables Among Adult Trauma Patients By Development Of Aki In Malawimentioning
confidence: 99%
“…Recently several studies have highlighted the important association of postoperative anaemia with outcomes, including acute kidney injury, major ischemic events, disability-free survival, and quality of recovery. 4,[20][21][22][23] There is a need to further delineate and clarify these associations -particularly the impact that interventions such as preoperative IV iron therapy may have on postoperative anaemia.…”
Section: Introductionmentioning
confidence: 99%